(untitled) (Al-Mansour Journal, 2023)
The Proposed Methodology Utilizing the relationship between Situational and attitudinal data to construct an approach of integrating models and sample design for generating attitudinal data as an attempt to prevent non-essential operation. Also as an imputation approach for missing data. The finding shows, that the proposed methodology could reduced the surveys cost between 20-30%. And the models been developed proved of highly results for imputation.